ChemInform Abstract: Gold(I)‐Catalyzed endo‐Selective Intramolecular α‐Alkenylation of β‐Yne‐Furans: Synthesis of Seven‐Membered‐Ring‐Fused Furans and DFT Calculations. Issue 23 (10th June 2014) - Dong, Zhe; Liu, Cheng‐Hang; Wang, Yi; Lin, Mu; Yu, Zhi‐Xiang
Abstract Six‐membered‐ring‐fused furans can also be obtained through exo‐selective cyclization for substrates with terminal alkynes [(XIII) and (XVIIa)] and alkynes bearing a CO2Me group [(XVIIb) and (XVIIc)].